Incidence of venous thromboembolism and use of anticoagulation in hematological malignancies: Critical review of the literature. (April 2018) - Annibali, Ombretta; Napolitano, Mariasanta; Avvisati, Giuseppe; Siragusa, Sergio
Abstract: Venous Thromboembolism (VTE) frequently complicates the course of hematologic malignancies (HM) and its incidence is similar to that observed in high-risk solid tumors. Despite that, pharmacologic prophylaxis and treatment of VTE in patients with HM is challenging, mainly because a severe thrombocytopenia frequently complicates the course of treatments or may be present since diagnosis, thus increasing the risk of bleeding. Therefore, in this setting, safe and effective methods of VTE prophylaxis and treatment have not been well defined and hematologists generally refer to guidelines produced for cancer patients that give indications on anticoagulation in patients with thrombocytopenia. In this review, besides to summarize the incidence and the available data on prophylaxis and treatment of VTE in HM, we give some advices on how to use antithrombotic drugs in patients with HM according to platelets count.